2001
DOI: 10.1097/00004703-200102000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Cognition, Academic Progress, Behavior and Self-Concept at 14 Years of Very Low Birth Weight Children

Abstract: The aim of this study was to compare cognition, academic progress, behavior, and self-concept children of very low birth weight (VLBW, birth weight < 1501 g) born in the period 1980 to 1982 with randomly selected children of normal birth weight (NBW, birth weight > 2,499 g). At 14 years of age, 130 (84.4%) of 154 VLBW and 42 (70.0%) of 60 NBW children were assessed. Ten VLBW children and one NBW child who had cerebral palsy were excluded. VLBW children scored at a significantly lower level on all three composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
140
0
5

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(160 citation statements)
references
References 16 publications
15
140
0
5
Order By: Relevance
“…None of the researchers observed reading disorders in isolation, but, in four articles, arithmetic problems were observed in isolation. 40,46 Seven of the 16 studies that detailed which academic subjects were affected reported problems with writing and spelling (dictation), which, in common with reading disorders, are learning problems related to language.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the researchers observed reading disorders in isolation, but, in four articles, arithmetic problems were observed in isolation. 40,46 Seven of the 16 studies that detailed which academic subjects were affected reported problems with writing and spelling (dictation), which, in common with reading disorders, are learning problems related to language.…”
Section: Resultsmentioning
confidence: 99%
“…Many authors 8,16,18,20,28,[39][40][41]46 reported associations between very low birth weight and cognitive deterioration, gauged by intelligence quotient. Weindrich et al 39 specified non-verbal intellectual compromise in eleven-year old schoolchildren, with significantly lower mean scores compared to those born weighing less than 2,500 g.…”
Section: Statistical Manual For Mental Disorders (Dsm-iv) Publishedmentioning
confidence: 99%
“…Cognitive Correlates Several studies of children with VLBW/VPTB have found that selective deficits in mathematics are accompanied by specific cognitive weaknesses, most often in the domains of visual spatial and perceptual motor abilities and executive function. Rickards et al (2001), for example, found deficits in mathematics but not in reading or spelling in comparing their VLBW cohort at age 14 years with a NBW group. The VLBW cohort also had impairments on tests of visual processing, visual memory, and visual perceptual organization, but not in most IQ subtests.…”
Section: Medical and Brain Correlatesmentioning
confidence: 99%
“…With respect to potential age differences in MD, impairments on tests of mathematics achievement in VLBW/ VPTB cohorts are evident from the early school-age years and persist into adolescence and young adulthood (Saigal et al, 1990;Taylor et al, 1995;Botting et al, 1998;Saigal et al, 2000;Rickards et al, 2001;Hack et al, 2002). To our knowledge, only two studies have examined changes in mathematics performance longitudinally in children with low birth weight.…”
Section: Sex and Age Differences In Mathematics Outcomesmentioning
confidence: 99%
“…[1][2][3][4] Children who were born preterm or small for gestational age have been found to be at risk for reduced cognitive test scores and to have higher rates of problems in memory, attention, and neuromotor function. 1,5,6 Very low birth weight (VLBW; Ͻ1500 g), especially, has been shown to be a risk and to predict school difficulties 4,7,8 and low academic achievement that was apparent still in young adulthood. [1][2][3][4] However, previous studies of general populations suggested that birth weight is associated with cognition and educational attainment across the full birth weight range.…”
mentioning
confidence: 99%